Utilizing extracted waterglass (socium silicate) from rice husk ash as alternative binder to inorganic silicate mineral paint - De Jesus, Xyanle Kriz L. (2018)
With the threat of global warming and climate change, the campaign for greener living has been profoundly promoting to save our environment for future generations. Prominent action involves waste utilization and management.The construction industry has adapted the concept of green architecture to lower carbon footprints by utilization of healthier materials and technology. Paint producers adopt low solvent and solvent-less technology in the past 40 years. Environmental regulations are becoming more stringent in all regions of the world to limit the emissions of Volatile Organic Compounds (VOCs) and hazardous air pollutants (HAPS).According to the report on Abandoned Biomass Resource Statistics of the Philippines, the country produces approximately 2360 metric tons of Rice Hull. Rice Hull Ash is composed of approximately 94% Silicone Oxide which constitutes to its slow degradation. After milling, that particular agricultural by product were most commonly set for burning. Direct combustion of the Rice Hull results to its end-product Rice Hull Ash. This ash is commonly end up underutilized as household as Dish cleanser or in land fill.This study extracted Sodium Silicate by chemically reacting to caustic soda Sodium Hydroxide to the Rice Hull Ash in 80-90°C. The Silicate was used as alternative binder to experimental group Inorganic Silicate Mineral Paint (ISMP). Several tests were conducted to determine the properties of the material in comparison to control group Commercially Available Flat Latex Paint (CAFLP). Test strips were used to determine its alkalinity. The material was subjected to 1-hour fire test to determine its resistivity. Tape test was used to determine its adhesion rating. Pencil test used the hardness of pencil graphite to determine the scratch hardness of the materials. Being inorganic in nature, the product has no VOC and NOx threats to space users and handlers. It also undertakes silicification process utilizes CO2 in the atmosphere. Its alkaline property is the responsible for the surface being less prone to microbial formation. Its density property is less dense which makes it lighter and has advantage in transportation. Its faster rate of drying saves construction time. It can with last the 1-hour fire resistivity test which is a major requirement in Concrete Construction Building Type. It has high adhesion rating means its properties can hold the pigment to the substrate. Hardness property is responsible for the minimum force to resist scratch. It garnered the softest score and failed the test compared to the Control Group.